EFL Teachers’ Perspectives on Learner Autonomy - Yuzulia, Irza; Yusuf, Fazri Nur (Universitas Swadaya Gunung Jati, 2019)
Teachers have a central role in fostering learner autonomy and their views regarding LA are essential. They should maintain the learning environment and activities to support LA. This research aimed to find out teachers’ attitudes towards their roles and learning practices to support LA. A questionnaire was administered to 19 teachers who are studying for a Masters degree at UPI. It is found that teachers rated their responsibilities in choosing classroom activities and evaluating students’ progress at the highest point. However, they viewed students’ decision making abilities in choosing learning objectives and evaluating their learning at the lowest score. Furthermore, the activities which teachers often recommended to are listen to English songs, read books and use the internet. It can be concluded that teachers have a strong belief towards their roles in LA. Even though they are already conscious about the importance of LA, it should be implemented into practice.